EVALUATION OF PROJECT-BASED LEARNING IMPLEMENTATION TO ENCOURAGE STUDENT CREATIVITY AND INNOVATION - Robby Cahyadi; Moh. Imron Rosidi; Nanang Abdillah (CV. ADIBA AISHA AMIRA, 2024)
Project-Based Learning (PBL) has been recognized as an effective approach to enrich the learning process by providing students with opportunities for in-depth exploration of real-world problems. The purpose of this study is to evaluate the implementation of PBL in enhancing students' creativity and innovation. This research examines how PBL can encourage students to develop critical thinking, collaboration and problem-solving skills that are relevant to the needs of today's working world. This study used the literature research method. The results show that PBL is successful in creating a more dynamic learning environment and stimulating student creativity. In many cases, students who engage in project-based learning show significant improvement in terms of the ability to think critically and innovatively. In addition, PBL also encourages the development of important 21st century skills such as teamwork, communication and independence. This study found that one of the keys to the success of PBL in enhancing students' creativity and innovation lies in the ability of educators to provide comprehensive challenges to students and keep them engaged in the learning process. However, challenges such as teacher readiness and limited learning time in some contexts are points that require further attention to maximize the effectiveness of PBL